Hydrogen substituted graphdiyne as carbon-rich flexible electrode for lithium and sodium ion batteries. Issue 1 (December 2017) - He, Jianjiang; Wang, Ning; Cui, Zili; Du, Huiping; Fu, Lin; Huang, Changshui; Yang, Ze; Shen, Xiangyan; Yi, Yuanping; Tu, Zeyi; Li, Yuliang
Abstract Organic electrodes are potential alternatives to current inorganic electrode materials for lithium ion and sodium ion batteries powering portable and wearable electronics, in terms of their mechanical flexibility, function tunability and low cost. However, the low capacity, poor rate performance and rapid capacity degradation impede their practical application. Here, we concentrate on the molecular design for improved conductivity and capacity, and favorable bulk ion transport. Through an in situ cross-coupling reaction of triethynylbenzene on copper foil, the carbon-rich frame hydrogen substituted graphdiyne film is fabricated. The organic film can act as free-standing flexible electrode for both lithium ion and sodium ion batteries, and large reversible capacities of 1050 mAh g−1 for lithium ion batteries and 650 mAh g−1 for sodium ion batteries are achieved. The electrode also shows a superior rate and cycle performances owing to the extended π-conjugated system, and the hierarchical pore bulk with large surface area. Flexible batteries have been used to power wearable smart electronics and implantable medical devices. Here, the authors report a carbon-rich flexible hydrogen substituted graphdiyne electrode exhibiting superior electrochemical performance in lithium and sodium ion batteries.